2017
DOI: 10.1080/10520295.2016.1259500
|View full text |Cite
|
Sign up to set email alerts
|

Immunocharacterization of matrix metalloproteinase-2 and matrix metalloproteinase-9 in canine transmissible venereal tumors

Abstract: Matrix metalloproteases (MMPs) are endogenous proteases that are responsible for degradation of extracellular matrix (ECM) proteins and cell surface antigens. The breakdown of ECM participates in the local invasion and distant metastases of malignant tumors. Canine transmissible venereal tumor (CTVT) is a naturally occurring contagious round cell neoplasm of dogs that affects mainly the external genitalia of both sexes. CTVT generally is a locally invasive tumor, but distant metastases also are common in puppi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
3
5
0
1
Order By: Relevance
“…Lately, MMP-2 has garnered attention by its correlation with the tumor invasion and formation of metastases (26). A recent study reported the presence of MMP-2 and -9 in the TVT tissue (22). The findings of this study supported the previous study and demonstrated that MMP-2 was strongly expressed by TVT cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Lately, MMP-2 has garnered attention by its correlation with the tumor invasion and formation of metastases (26). A recent study reported the presence of MMP-2 and -9 in the TVT tissue (22). The findings of this study supported the previous study and demonstrated that MMP-2 was strongly expressed by TVT cells.…”
Section: Discussionsupporting
confidence: 92%
“…MMP-7 is elevated in numerous human primary cancer types (21). As only one study is available about the MMP-2 expression in TVT, the knowledge about the MMP-7 reaction in TVT is lacking (22).…”
Section: Mmp-2 (Gelatinase A)mentioning
confidence: 99%
“…Elimination of the ECM proteins that surround the tumor cells is an important step for metastasis. (Akkoc et. al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Increased concentrations of MMPs have been associated with invasion, metastasis and poor prognosis in many malignancies of humans (Loukopoulos et al, 2003;Aresu et al, 2011). MMP-2 and MMP-9 are the most studied proteases in cancer biology (Akkoc et al, 2017). Although TVT has a very low capacity to metastasize, it can metastasize to many tissues and organs such as liver, kidney, spleen, eyes, brain, pituitary gland, skin, subcutis, mesenteric lymph nodes and peritoneum (Tiwari et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation